A permeability model for gas flow in coal considering the water content and slippage effect. (9th July 2021) - Li, Jianhua; Li, Bobo; Xu, Jiang; Wang, Zhihe; Gao, Zheng; Zhang, Yao
Coal seams are usually in a state of gas-water coexistence and for coal-bed methane (CBM) reservoirs, coal permeability is essential to the extraction process of CBM. The purpose of this study is to experimentally analyse the coal permeability characteristics under different water content conditions and to propose a permeability model for gas flow in coal seams. Experiment results show that when the pore pressure is fixed, the gas adsorption decreases with the increase of water content. Similar behaviour is also found for the adsorption deformation which can discourage the coal permeability. In the process of increasing pore pressure, under the control of sorption-induced deformation and slippage effect, the permeability of coal shows a trend of decreasing first and then tending to be gentle. In addition, based on gas flow experiments, an improved permeability model considering water content and slippage effect is established based on the classic matchstick model. We also proposed a calculation model of slip factor considering the influence of water content. Wherein, the slippage factor showed an increasing trend under the combined effect of water content and pore pressure.